Resilience and professional identity among F-2 visa spouses in the United States: Coping with career constraints under immigration policies - Bakhshalizdeh, Fatemeh (Journal of International Students, 2025)
Previous scholars highlighted how F-2 visa regulations interrupt the career of spouses of international students by preventing them from working, but they did not explore the coping strategies of this population in maintaining their professional identity, and how these coping strategies show the traces of feminization of poverty. Through participant observation and interviewing 16 female F-2 visa holders who used to work before coming to the US, and inspired by Abu-Lughod's (1990) concept of resistance, this article shows that F-2 visa regulations have some negative effects on the identity. However, the participants use different coping strategies, such as trying to go to universities/enter job market through change of immigration status, taking opportunities to receive gift cards in return for their work/services, and not acknowledging change in their professional identity; these coping strategies show F-2 visa regulations with other policies contribute to feminization of poverty mainly by postponing the employment.